SEXUAL BEHAVIOR AND KNOWLEDGE LEVEL OF COMMERCIAL SEX WORKERS INFLUENCE THE SPREAD OF SEXUALLY TRANSMITTED INFECTIONS - Rochman Mujayanto; Erdianto Setya Wardhana (Faculty of Dentistry, Universitas Islam Sultan Agung, 2019)
Background : Sexually transmitted infections (STIs) are commonly found in commercial sex workers (CSWs) due to lack of knowledge and bad behavior in sexual intercourse. STI does not only cause symptoms in the genital area but also lesions in the oral cavity. Method : This research was an analytical survey with cross sectional approach. Samples were 110 CSWs selected by simple random sampling. Chi-Square test was used to see the difference in the influence of the level of knowledge and sexual behavior on the incidence of oral cavity lesions. Result: Oral cavity lesions related to STIs were found in 44 cases, including suspect oral candidiasis, ulcers, suspect linear gingival erythematous (LGE), Suspect Kaposi Sarcoma and Oral Hairy Leukoplakia. Lesions were found in 43.9% respondents with low knowledge level and 37.7% in good knowledge level. Chi-Square test obtained p value of 0.328 (p> 0.05) showed that there was no difference between the knowledge level and the occurrence of lesions. Lesions were found 94.1% in respondents with bad sexual behavior and 15.8% in respondents with good sexual behaviour. Chi-Square test obtained p value of 0.00 (p> 0.05) which means that there are significant differences between good sexual behavior respondents and bad sexual behavior respondents towards the presence of lesions. Conclusion: The level of knowledge was not a risk factor for oral lesions, whereas bad sexual behavior was a risk factor for oral cavity lesions.